Upaya Meningkatkan Hasil Belajar Persamaan Garis Lurus melalui Penerapan Strategi Pembelajaran Snow Balling - Dewi Annisa (Departement of Mathematics Education, 2020)
Students' diverse abilities, both in terms of knowledge, and speed in receiving lessons, can be overcome by applying a cooperative learning model. One of them is the snow balling learning strategy, where in this lesson students can discuss problems and then solve them together with group friends. This study was conducted to determine whether there was an increase in student learning outcomes and activities during the implementation of the snow balling learning strategy in class VIII-B of SMPN 236 Jakarta, especially on the subject of straight line equations. The intended student learning outcomes are viewed in terms of cognitive, while student activities are viewed from the number of activities carried out during material explanation and group discussions. This study used a qualitative approach with the type of classroom research conducted in class VIII-B of SMPN 236 Jakarta. The results showed that the application of the snow balling learning strategy could improve the learning activities and mathematics learning outcomes of students as indicated by the increase in students' test scores from the initial test to the final test of activity III. The mean score of the initial test was 49.2; the final test of activity I was 54.6; the activity test II was 65.7, the activity test III was 73.5. The percentage of the number of students who met the minimum completeness criteria (KKM) also increased, namely 13.04% in activity I, 45.83% in activity II, and 58.33% in activity III. The KKM of mathematics subject at SMPN 236 Jakarta is 75. The results of this study indicate that the application of the snow balling learning strategy is an alternative in selecting cooperative learning strategies that can be applied in the classroom by teachers with the aim of increasing learning outcomes and student activities in the learning process.